Chen's Attractor in Music Composition - Wainiya, Wasin; Sooraksa, Pitikhate (My University, 2018)
Algorithmic composition has been developed by using various methods. For example, one may use mathematical models to generate musical signals as melodies. Chaotic equations may also be used for the composition. In this paper, Chen's attractor is employed to generate the sequences of melodies and patterns by applying "the event" theory.
Keywords: Algorithmic Composition; Chaos; Chen's Attractor